2017
DOI: 10.1371/journal.pone.0188909
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human IL-26 facilitates the innate immune response to endotoxin in the bronchoalveolar space of mice in vivo

Abstract: Interleukin (IL)-26 is released in response to bacterial endotoxin (LPS) in the bronchoalveolar space of humans in vivo and it may potentiate neutrophil chemotaxis by enhanced IL-26 receptor stimulation. However, the effects of extracellular IL-26 protein on the innate immune response in the lungs in vivo remain unknown. Here, we characterized these effects of IL-26 on a wide range of aspects of the innate immune response to LPS in different compartments of the lungs in vivo over time. We administrated recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“… 15 Therefore, murine cell lines or mouse models have been used to further unravel the mechanisms of IL-26 and to study the effect of IL-26 in vivo. 15 , 24 , 25 Moreover, the results of these studies were in line with findings obtained in human in vitro experiments. To assess the role of IL-26 in vivo in the context of neuroinflammation, we administered rhIL-26 to EAE mice immunized with MOG 35–55 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“… 15 Therefore, murine cell lines or mouse models have been used to further unravel the mechanisms of IL-26 and to study the effect of IL-26 in vivo. 15 , 24 , 25 Moreover, the results of these studies were in line with findings obtained in human in vitro experiments. To assess the role of IL-26 in vivo in the context of neuroinflammation, we administered rhIL-26 to EAE mice immunized with MOG 35–55 .…”
Section: Discussionsupporting
confidence: 87%
“… 15 Previous studies on IL-26 have shown that results obtained from mouse models using rhIL-26 provide information, which is supportive of human in vitro or in situ studies. 15 , 24 , 25 Before investigating the contribution of IL-26 on BBB permeability in vivo, we first sought to confirm whether rhIL-26 affects mouse BBB ECs in vitro. Mouse brain ECs were isolated and treated with 100 ng/mL rhIL-26, and subsequent expression of TJ molecules JAM-1, ZO-1, and CLDN5 was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…4 It potentiates the chemotactic response of human neutrophils in vitro and enhances endotoxin-induced accumulation of neutrophils and macrophages in the airways in vivo. 4,5 It also displays direct antibacterial properties in experimental models in vitro and in vivo. 6 Moreover, there is evidence for enhanced IL-26 protein in the airways for poorly controlled compared with controlled asthma, among children with the noneosinophilic endotype.…”
Section: To the Editormentioning
confidence: 99%
“….47 Total lymphocyte count 3 10 60.29 (0.09-0.65) 0.35 (0.12-0.71) .74 Lymphocyte proportion (%) 5 (3-6) 4 (2)(3)(4)(5)(6) .47 Total macrophage count 3 10 66.3 (3.2-9.8) 10.0 (5.5-11.5) .32 Macrophage proportion (%) 90 (87-92) 92 (89-95) .34 Total eosinophil count 3 10 60.05 (0.00-0.18) 0.00 (0.00-0.11) .24 Eosinophil proportion (%) 1 (0-2) 0 (0-1) .16 Total neutrophil count 3 10 60.12 (0.04-0.26) 0.26 (0.16-0.41) .055 Neutrophil proportion (%)…”
mentioning
confidence: 99%
“…In mice, exposure to endotoxin enhances the production of IL-26, IL-6 and IL-8 in the airways. 40 We observed a positive correlation between IL-26 and sputum neutrophils, suggesting an enhanced recruitment of these cells in severe asthma with a possible role of microbial agents. Virus are reported as a major factor of asthma exacerbation, inducing non-specific innate immunity activation involving Th17 cytokines.…”
Section: Discussionmentioning
confidence: 56%